Physics teaching in youth and adult education: paths and reflections - Siqueira, Kleber Saldanha de (Diversitas Journal, 2023)
Historically in Brazil, education aimed at young people and adults was characterized by the formation of subjects prepared for professional practice, considering the different stages of Brazilian industrial development. Over the decades, this need continued to permeate educational initiatives and public policies, with few humanistic developments. However, with the changes generated by the economic scenario of the last 40 years, thinking about an Education for Youth and Adults only aimed at the universe of work means restricting the potential and social protagonism of these subjects. In view of this, based on modern conceptions about Youth and Adult Education, we seek in this article to reflect on the teaching of Physics in this teaching modality, highlighting the role of this field of science in the scientific and emancipatory education of citizens, educated, able to professional exercise, and able to understand the nature around them. The role of Physics in the professional and school training of these subjects will be discussed in a critical-reflective manner, highlighting the teacher's pedagogical role in teaching the different contents that characterize the curriculum of this discipline in view of the current training parameters that guide this modality. This study has a narrative bibliographic qualitative character, presenting results of research carried out in the last decade, reverberating the important role of Science Teaching in schooling for social exercise and for the world of work, contrasting with the old conceptions based solely on filling jobs.